2014
DOI: 10.1016/j.jceh.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages from Patients with Cirrhotic Ascites Showed Function Alteration of Host Defense Receptor

Abstract: Background: Patients with cirrhotic ascites (PCA) are susceptible to spontaneous bacterial peritonitis (SBP) which has increased morbidity and mortality. Since some host defense aspects of peritoneal macrophages (PMv) from PCA are altered this study examined factors related to receptor-mediated phagocytosis. Methods: Twelve PCA were studied. PMɸ were isolated from ascitic fluid (AF) samples removed from these patients. Uptake of mannose receptor (MR)-specific ligand, fluorescein isothiocyanate-mannosylated-bov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…bacteria) these cells produce a host of inflammatory signals including cytokines and lipid mediators that lead to vascular leakage and leukocyte recruitment (Hellmann et al, 2015). In addition, these cells also actively participate in clearance of invading pathogens and alteration in their phenotype impairs their ability to clear bacteria and leads to a dysregulated inflammatory response in experimental systems (Dahdah et al, 2014) and humans (Ahmed et al, 2014). In the present study we found that administration of PCTR1 to vagotomised mice 16h prior to challenge at a dose as low as 75ng/mouse restored the macrophage phenotype as well as phagocytic function.…”
Section: Discussionmentioning
confidence: 99%
“…bacteria) these cells produce a host of inflammatory signals including cytokines and lipid mediators that lead to vascular leakage and leukocyte recruitment (Hellmann et al, 2015). In addition, these cells also actively participate in clearance of invading pathogens and alteration in their phenotype impairs their ability to clear bacteria and leads to a dysregulated inflammatory response in experimental systems (Dahdah et al, 2014) and humans (Ahmed et al, 2014). In the present study we found that administration of PCTR1 to vagotomised mice 16h prior to challenge at a dose as low as 75ng/mouse restored the macrophage phenotype as well as phagocytic function.…”
Section: Discussionmentioning
confidence: 99%